One-year outcomes in cardiogenic shock triggered by supraventricular tachycardia: an analysis of the FRENSHOCK multicenter prospective registry - Cherbi, Miloud; Bonnefoy, Eric; Lamblin, Nicolas; Gerbaud, Edouard; Bonello, Laurent; Roubille, François; Levy, Bruno; Champion, Sebastien; Lim, Pascal; Schneider, Francis; Elbaz, Meyer; Khachab, Hadi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiogenic shock (CS) is the most severe form of heart failure (HF), resulting in high early and long-term mortality. Characteristics of CS secondary to supraventricular tachycardia (SVT) are poorly reported. Based on a large registry of unselected CS, we aimed to compare 1-year outcomes between SVT-triggered and non-SVT-triggered CS. Methods FRENSHOCK is a French prospective registry including 772 CS patients from 49 centers. For each patient, the investigator could report 1–3 CS triggers from a pre-established list (ischemic, mechanical complications, ventricular/supraventricular arrhythmia, bradycardia, iatrogenesis, infection, non-compliance, and others). In this study, 1-year outcomes [rehospitalizations, mortality, heart transplantation (HTx), ventricular assist devices (VAD)] were analyzed and adjusted for independent predictive factors. Results Among 769 CS patients included, 100 were SVT-triggered (13%), of which 65 had SVT as an exclusive trigger (8.5%). SVT-triggered CS patients exhibited a higher proportion of male individuals with a more frequent history of cardiomyopathy or chronic kidney disease and more profound CS (biventricular failure and multiorgan failure). At 1 year, there was no difference in all-cause mortality (43% vs. 45.3%, adjusted HR 0.9 (95% CI 0.59–1.39), p = 0.64), need for HTx or VAD [10% vs. 10%, aOR 0.88 (0.41–1.88), p = 0.74], or rehospitalizations [49.4% vs. 44.4%, aOR 1.24 (0.78–1.98), p = 0.36]. Patients with SVT as an exclusive trigger presented more 1-year rehospitalizations [52.8% vs. 43.3%, aOR 3.74 (1.05–10.5), p = 0.01]. Conclusion SVT is a frequent trigger of CS alone or in association in more than 10% of miscellaneous CS cases. Although SVT-triggered CS patients were more comorbid with more pre-existing cardiomyopathies and HF incidences, they presented similar rates of mortality, HTx, and VAD at 1 year, arguing for a better overall prognosis. Clinical Trial Registration https://clinicaltrials.gov, identifier: NCT02703038.